The role of apoptosis in pituitary adenomas in the field of conventionally used therapeutic approaches - Cerman, Jaroslav; Cap, Jan; Marekova, Martina; Nemecek, Stanislav; Marek, Josef; Rudolf, Emil; Cervinka, Miroslav (Annals of the New York Academy of Sciences, 2003)
The aim of the study was to investigate the mechanism of action of somatostatin analogues (SSA), ionizing radiation, and their combination on pituitary adenoma cells with special emphasis on proliferative and apoptotic activity. In the 14 GH-secreting adenomas pretreated with SSA before surgery, more prominent regressive changes were found accompanied by compensatory increase in perivascular fibrosis than in the reference group of 17 unpretreated adenomas. The proliferative Ki-67 labeling index was significantly lower in the treated group (median 1.6 per 1000) than in the untreated patients (median 5.0 per 1000). Apoptosis was detected in only 2 of the 14 pretreated adenomas, and it was more frequent (9/17) and more prominent in the untreated group. In cell lines, the SSA had minimal antiproliferative effect, and they were unable to induce apoptosis. Ionizing radiation at doses of 5-20 Gy induced apoptosis in the corticotroph cell line AtT20 with no cell-cycle block. In the somatotroph GH3 cell line, the early (premitotic) apoptosis was detectable using only a high dose of 200 Gy; after irradiation with doses of 20-50 Gy, apoptosis appeared with the latency of 48-72 hours, and was preceded by cell-cycle arrest in the G(2)/M phase. The treatment with somatostatin-14 during irradiation increased the percentage of apoptotic cells in culture 10 days after irradiation (11% versus 3% using 20 Gy).
Keywords: Pituitary Neoplasms; adenom; buněčné dělení; buněčný cyklus; Adenoma; Biomarkers, Tumor; apoptóza; Humans; lidé; nádorové biomarkery; Cell Division; nádory hypofýzy; Apoptosis; Cell Cycle